2023
DOI: 10.1186/s12871-023-01997-2
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil to lymphocyte ratio and platelet to lymphocyte ratio as prognostic predictors for delirium in critically ill patients: a systematic review and meta-analysis

Abstract: Introduction In this systematic review and meta-analysis, we aim to analyze the current literature to evaluate neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) values among critically ill patients who develop delirium as compared to those who do not. Methods PubMed, Web of Science, and Scopus were used to conduct a systematic search for relevant publications published before June 12, 2022. The Newcastle–Ottawa scale was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 80 publications
0
1
0
Order By: Relevance
“…The study emphasises that systemic inflammation and oxidative stress play an important role in the pathophysiology of delirium [ 29 ]. Higher NLR levels might indicate inflammation and neuro-inflammation making patients more susceptible to delirium in the care unit (ICU) environment [ 30 ]. Our results showed that the value of NLR was significantly higher for patients with delirium (11.9 vs 8.7, p < 0.001) so we believe NLR may be a useful tool in early diagnosis of delirium in critically ill patients with urosepsis.…”
Section: Discussionmentioning
confidence: 99%
“…The study emphasises that systemic inflammation and oxidative stress play an important role in the pathophysiology of delirium [ 29 ]. Higher NLR levels might indicate inflammation and neuro-inflammation making patients more susceptible to delirium in the care unit (ICU) environment [ 30 ]. Our results showed that the value of NLR was significantly higher for patients with delirium (11.9 vs 8.7, p < 0.001) so we believe NLR may be a useful tool in early diagnosis of delirium in critically ill patients with urosepsis.…”
Section: Discussionmentioning
confidence: 99%
“…A wealth of evidence suggests that delirium may contribute to dementia through several mechanisms, such as inflammation [ 41 , 42 ]. Indeed, elevation to peripheral markers of inflammation, including NLR, has been found to be related with delirium occurrence [ 43 , 44 ]. Longitudinal investigations in patients with dementia may help to establish if NLR may be a predictive biomarker for delirium.…”
Section: Discussionmentioning
confidence: 99%
“…Delirium in older adults following hip fracture surgery is associated with increased white blood cell numbers and neutrophil/lymphocyte ratio indicating aseptic inflammation ( 11 ). A recent meta-analysis shows that the delirium diagnosis is associated with a higher neutrophil/lymphocyte ratio in various critical care settings ( 12 ). Furthermore, we showed that delirium is characterized by IRS activation and a relative deficiency in the compensatory immunoregulatory system (CIRS), which prevents hyperinflammation ( 13 ).…”
Section: Introductionmentioning
confidence: 99%